The Effect of a 12-Week Moderate Intensity Interval Training Program on the Antioxidant Defense Capability and Lipid Profile in Men Smoking Cigarettes or Hookah: A Cohort Study - Abdessalem Koubaa; Moez Triki; Hajer Trabelsi; Hamza Baati; Zouhair Sahnoun; Ahmed Hakim (The Scientific World Journal)
Aim. To examine the impact of interval training program on the antioxidant defense capability and lipid profile in men smoking cigarettes or hookah unable or unwilling to quit smoking. Methods. Thirty-five participants performed an interval training (2 : 1 work : rest ratio) 3 times a week for 12 weeks at an intensity of 70% of VO2max. All subjects were subjected to a biochemical test session before and after the training program. Results. The increase of total antioxidant status (TAS), glutathione peroxidase (GPx), and α-tocopherol, is significant only for cigarette smokers (CS) and hookah smokers (HS) groups. The decrease of malondialdehyde (MDA) and the increase of glutathione reductase (GR) are more pronounced in smokers groups compared to those of nonsmokers (NS). Superoxide dismutase (SOD) increases in NS, CS, and HS groups by 10.1%, 19.5%, and 13.3%, respectively (P<0.001). Likewise, a significant improvement of high-density lipoprotein cholesterol (HDL-C) and TC/HDL-C ratio was observed in CS and HS groups (P<0.05). Conclusion. Although the interval training program does not have a significant effect on blood lipid levels, it seems to be very beneficial in the defense and prevention programs of oxidative stress.